Gel Formulation of Ethyl Acetate Garlic Extraction and Its Activity Against Staphylococcus Epidermis - Khairan, Khairan (Journal of Chemical Natural Resources, 2019)
Garlic is known to have antibacterial and antifungal activities. This research aims to formulate the gel materials extracted from the garlic and to investigate the antimicrobial activities to Staphylococcus epidermidis. The phytochemical screening showed that the gel materials of ethyl acetate consisted alkaloid, flavonoid, and saponin substances. The formulation of gel was synthesized with different variations of 1, 5, and 10%. In this research, the gel materials were analyzed to understand the stability, homogeneity, pH, viscosity and dispersive powers. The results showed that good abilities of gel based on the taste, aroma and consistency, while the homogeneity property of each samples is influenced by the presence of gel concentration. The viscosity property of gels accounted for 3201.02-1664.04 Cps with 2.95-3.8 cm of dispersive powers. The ability of antimicrobial showed that higher concentration of 5% and 10% gels showed greater inhibitory zones of 18,10 and 22,08 mm compared to 1% of concentration